2019
DOI: 10.1371/journal.pcbi.1006953
|View full text |Cite
|
Sign up to set email alerts
|

Passenger mutations accurately classify human tumors

Abstract: Determining the cancer type and molecular subtype has important clinical implications. The primary site is however unknown for some malignancies discovered in the metastatic stage. Moreover liquid biopsies may be used to screen for tumoral DNA, which upon detection needs to be assigned to a site-of-origin. Classifiers based on genomic features are a promising approach to prioritize the tumor anatomical site, type and subtype. We examined the predictive ability of causal (driver) somatic mutations in this task,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 45 publications
3
72
0
Order By: Relevance
“…In this validation setting, we applied such genomic classifiers to a problem of ‘one-versus-one’ classification, where we contrasted the originally assigned cancer type versus the newly-proposed cancer type for each reassignment. We found that such one-versus-one classifiers based on genomic data had satisfactory accuracy with our whole-exome sequencing data sets (Fig S4; our past work (24) suggests whole genome sequences are more powerful). Finally, we included an additional classifier based on copy number alteration (CNA) profiles, which were also shown to yield accurate predictive models of tissue specificity (24,25).…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…In this validation setting, we applied such genomic classifiers to a problem of ‘one-versus-one’ classification, where we contrasted the originally assigned cancer type versus the newly-proposed cancer type for each reassignment. We found that such one-versus-one classifiers based on genomic data had satisfactory accuracy with our whole-exome sequencing data sets (Fig S4; our past work (24) suggests whole genome sequences are more powerful). Finally, we included an additional classifier based on copy number alteration (CNA) profiles, which were also shown to yield accurate predictive models of tissue specificity (24,25).…”
Section: Resultsmentioning
confidence: 56%
“…We next turned to support individual examples of cell lines with reassigned tissue identity by analyzing independent data. In particular, we used genomic sequence-based classifiers, which are able to predict the tissue of origin based on mutation patterns (24,25). As in our recent work (24), we used the trinucleotide mutation spectra and the oncogenic mutations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations